Preparation of Ag/Cu Janus Nanowires: Electrodeposition in Track-Etched Polymer Templates - ZHU 1, X.R.; WANG 2, C.M.; XUE 2, J.M.; FU 2, Q.B.; JIAO 1, Z.; WANG 1, W.D.; QIN 1, G.Y. (Asian Journal of Chemistry, 2017)
The authors retract the above article for violations of the ethical guidelines to publication. This article was published without the knowledge or consent of the authors.As a result, the authors retract this manuscript